DNA Barcoding of Plants Within The Malvaceae Family - Yap, Le Xian (2017)
Nowadays, demand for medical plants has increased due to some side effects in synthetic drugs. This has led to some companies using plants with similar appearance as a replacement to make herbal products, and this has reduced the effect and quality of the drug. To solve this problem, a strong and reliable authentication method is required in order to differentiate the real from the fake medical plants. DNA barcoding is one of the suitable methods that can be used to identify the species of plant. It has a very high reproducibility with medium cost and ease of use in differentiation of plant. In this study, Hibicius rosa-sinensis (with a single layer of white petals), H. cannabinus L and Malavaviscus arbireus var drummondii all of which belong to Malvaceae family and are said to have medical functions, were used. The DNA barcode markers that were used in this study to define the ability in differentiation of plant species are matK and trnH-psbA. The method of extracting DNA is and adaption of a standard protocol which was established by Edwards, Johnstone & Thompson in 1991. and was successful in Malvaceae inspite of their high polysaccharide content. Amplification of the matK and trnH-psbA sequence was successful and good quality sequences were obtained. While BLAST resulted in some ambiguities in identification, but the phylogenetic tree based on both matK and tranH-psbA clearly clustered samples of each species into the same clade with high bootstrap value of over 70%. However , when including the downloaded sequence of related species, only Hibiscus rosa-sinensis can clearly clustered into the same clade. Therefore, both the matK and trnH-psbA have potential to differentiate each species of plant from others. Further study should be done by using larger samples size from different geographical areas and using others marker (such as a nuclear marker)